Bromelain improved cognitive & mood behaviors, oxido-inflammatory indices and cholinergic transmission in scopolamine-induced neurotoxicity in male wistar rats.: Bromelain reduced scopolamine neurotoxicity. (Nigerian Journal of Physiological Sciences, 2024)
Alzheimer’s disease (AD) is associated with pathophysiological and psychological disturbances including cognitive decline, depression, anxiety and motor imbalance. Conventional drugs for managing AD do not address associated non-neurocognitive co-morbidities, hence the need to investigate alternative therapies especially from plants. The neuroprotective benefits of bromelain have been identified, but its impacts on scopolamine-induced neurotoxicity is yet to be elucidated. Twenty-Five male rats were separated randomly into 5 groups: Control (normal saline; 1ml/kg); Scopolamine (i.p; 1mg/kg); Bromelain (50mg/kg); Scopolamine + Bromelain; Scopolamine + Donepezil (reference drug, 1mg/kg). Neurobehavioral paradigms (novel object recognition, elevated plus maze, forced swimming and open field tests were assessed, followed by biochemical (MDA, SOD, AChE, NO, Total protein & IL-1b) assay in the PFC. Data were analyzed using one-way ANOVA (Tukey’s posthoc.). Values with p